Análisis del impacto adverso de la marginación social en las perspectivas del desarrollo humano en Morelia, Michoacán - García Gómez, Alejandra (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Despite evident improvements in the residential conditions of Morelia, including the reduction of homes with basic deficiencies, a connection persists between educational lag, income levels, and economic opportunities, creating a cycle that limits options and impacts income distribution. This study aims to establish the relationship between social marginalization and the perception of human development in Morelia, Michoacán. In the theoretical framework, a thorough review aligned with the research was conducted, identifying relevant theoretical frameworks. In the methodological phase, the choice of a survey as a measurement instrument was supported by related literature. The Likert scale was used as a measurement technique, supported by its application in surveys to assess attitudes and perceptions. The key finding is that perception varies according to the situation, educational level, and income. Those with lower education perceive that high levels are not required for a good quality of life, in contrast to those with higher education. In lower-income brackets, a modest increase is considered sufficient, while in higher-income brackets, perception differs. This discovery supports the need for specific interventions. As a recommendation, it is suggested to generate educational and employment options for the unemployed or informal workers who face obstacles in accessing social security. Addressing educational lag through regularization programs and transitioning to formal employment to ensure rights and benefits emerge as a fundamental strategy.

A pesar de mejoras evidentes en las condiciones residenciales de Morelia, incluyendo la reducción de viviendas con carencias básicas, persiste una conexión entre rezago educativo, ingresos y oportunidades económicas, generando un ciclo que limita opciones e impacta la distribución del ingreso. Este estudio busca establecer la relación entre la marginación social y la percepción del desarrollo humano en Morelia, Michoacán. En el marco teórico, se realizó una revisión exhaustiva alineada con la investigación, identificando marcos teóricos relevantes. En la fase metodológica, la elección de la encuesta como instrumento de medición se respaldó con literatura afín. La escala Likert se usó como técnica de medición, respaldada por su aplicación en encuestas para evaluar actitudes y percepciones. El hallazgo clave es que la percepción varía según la situación, nivel educativo e ingresos. Quienes tienen menos educación perciben que no se requieren niveles elevados para una buena calidad de vida, en contraste con los más educados. En ingresos bajos, se considera que un aumento modesto es suficiente, mientras que, en ingresos altos, la percepción es diferente. Este descubrimiento respalda la necesidad de intervenciones específicas. Como recomendación, se sugiere generar opciones educativas y de empleo para desempleados o informales que presentan un obstáculo en el acceso a seguridad social. Abordar el rezago educativo mediante programas de regularización y transicionar a empleo formal para garantizar derechos y prestaciones emerge como estrategia fundamental.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias del Desarrollo Regional
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2024-0805; Oportunidades; Desigualdades; Percepción; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18706